2017
DOI: 10.1055/s-0037-1603939
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Determination of Human Chorionic Gonadotropin in Vaginal Washings for the Early Diagnosis of Premature Rupture of Fetal Membranes

Abstract: Keywords► human chorionic gonadotropin ► β subunit ► premature rupture of fetal membranes ► diagnosis ► obstetrics ► pregnancy complications AbstractPurpose This study aimed to evaluate and validate the qualitative human chorionic gonadotropin β subunit (β-hCG) test of the vaginal fluid washings of pregnant women with premature rupture of fetal membranes (PROM).Methods Cross-sectional study of pregnant women between gestational weeks 24 and 39 who underwent consultations in one of our institutions. They were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In a study by [23] , analysis was performed on 177 pregnant women with confirmed membranes status, the major cut-off point studied was of 100 mUI/mL, and it provided a sensibility of 71.2%, a specificity of 100%, a PPV of 100%, and an NPV of 65.1%; even though there was a high specificity with this cut-off point, it showed lower sensibility.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by [23] , analysis was performed on 177 pregnant women with confirmed membranes status, the major cut-off point studied was of 100 mUI/mL, and it provided a sensibility of 71.2%, a specificity of 100%, a PPV of 100%, and an NPV of 65.1%; even though there was a high specificity with this cut-off point, it showed lower sensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clinical examination still has a weakness in accurately diagnosing PROM. 4 An accurate diagnostic method by injecting a dye into the amnion is invasive; therefore, it is not routinely performed. 3 Noninvasive diagnostic procedures, such as biochemical markers, may help diagnose PROM.…”
Section: Introductionmentioning
confidence: 99%
“…However, those biomarkers cannot be applied as diagnostic tools due to their cost and complexity. 3,4 In contrast, Betahuman chorionic gonadotropin (beta-hCG) is thought to be a more accurate marker of PROM, especially in cases with the ruptured membrane in peripheral or covert areas. [5][6][7][8][9][10] Beta-hCG is a glycoprotein produced by the placental syncytiotrophoblast found in the amniotic fluid, maternal blood, and urine.…”
Section: Introductionmentioning
confidence: 99%
“…Premature rupture of fetal membranes (PROM), the leakage of amniotic fluid prior to labour irrespective of gestational age, occurs in 2-25% of all pregnancies, while PROM before 37 weeks of gestation occurs in nearly 3% of all pregnancies and referred to as preterm PROM (PPROM) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition and appropriate treatment of PPROM is crucial for preventing potential adverse perinatal outcomes related to prematurity (i.e. neonatal morbidity and mortality) and for minimizing the risk of fetal and maternal complications [3][4][5][6]. However, PPROM continues to be a challenging condition in current obstetric practice in terms of controversies regarding the optimal timing and route of delivery to minimize maternal and perinatal morbidity [3,5].…”
Section: Introductionmentioning
confidence: 99%